2018
DOI: 10.3389/fphys.2018.00506
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Reactive Agility and Change of Direction Speed in Differentiating Performance Levels in Junior Soccer Players: Reliability and Validity of Newly Developed Soccer-Specific Tests

Abstract: Agility is a significant determinant of success in soccer; however, studies have rarely presented and evaluated soccer-specific tests of reactive agility (S_RAG) and non-reactive agility (change of direction speed – S_CODS) or their applicability in this sport. The aim of this study was to define the reliability and validity of newly developed tests of the S_RAG and S_CODS to discriminate between the performance levels of junior soccer players. The study consisted of 20 players who were involved at the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
125
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(149 citation statements)
references
References 44 publications
10
125
4
2
Order By: Relevance
“…Comparable to the importance of linear sprint ability, the ability to efficiently change direction and velocity is also of significance to soccer performance (Pojskic et al, 2018), due to its multidimensional nature (Stølen et al, 2005;Strudwick et al, 2002). As discussed previously (Section 2.2.1.1), high intensity activity (including sprinting, accelerations, decelerations, and COD) has increased substantially during match play in senior soccer (Barnes et al, 2014;Bush et al, 2015).…”
Section: Evaluating Running Characteristics Of Soccer -Cod/agilitymentioning
confidence: 99%
“…Comparable to the importance of linear sprint ability, the ability to efficiently change direction and velocity is also of significance to soccer performance (Pojskic et al, 2018), due to its multidimensional nature (Stølen et al, 2005;Strudwick et al, 2002). As discussed previously (Section 2.2.1.1), high intensity activity (including sprinting, accelerations, decelerations, and COD) has increased substantially during match play in senior soccer (Barnes et al, 2014;Bush et al, 2015).…”
Section: Evaluating Running Characteristics Of Soccer -Cod/agilitymentioning
confidence: 99%
“…The validation of the tests that comprise the FITescola ® battery and the reliability of some tests, such as the 20 m shuttle run, horizontal jump, 4 × 10 m shuttle run, push‐up test and the sit and reach has been previously examined in youth (general population) (Artero et al, 2011; Baumgartner, Oh, Chung, & Hales, 2002; Ortega, Artero, et al, 2008; Ruiz et al, 2011; Vanhelst et al, 2016). Although some of the tests comprising the FITescola ® battery (e.g., the speed test) were tested for reliability in athlete samples from specific sports (e.g., football) (Pojskic et al, 2018), the reliability of the FITescola ® battery as a whole was never tested among young athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The COD tests examined within this study demonstrated a better intersession reliability than previously reported [18,28,50]. The better reliability demonstrated could potentially be explained due to the high performance standard of this sample, previously proposed as an influencer of test reliability in adolescent athletes [35,51].…”
Section: Discussionmentioning
confidence: 44%
“…Considering the varied physical demands imposed by different COD tests [10,15,16], the shorter test duration and singular acute change of direction may explain the improved intersession reliability we observed for the Y-SprintPRE compared to previous research [28,50]. The ability to change direction is angle dependent and affected by entry velocity into the COD [10,15,16].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation